In vitro anticancer activity of silver nanoparticles phyto-fabricated by Hylocereus undatus peel extracts on human liver carcinoma (HepG2) cell lines. (May 2022) - Shyamalagowri, S.; Charles, P.; Manjunathan, J.; Kamaraj, M.; Anitha, R.; Pugazhendhi, A.
Abstract: Every year, millions of people die from cancer, and most anticancer medications have a low specificity of action and significant toxicity, resulting in severe side effects. As a result, the discovery of effective anticancer drugs is a top priority. Hence, the focal point of this research is to synthesize the dragon fruit peel aqueous extract fabricated silver nanoparticles (DFPAE-AgNPs) in a facile and green chemistry approach as a new-fangled anticancer agent. The selected primary phytochemicals are qualitatively screened for their presence in dragon fruit peel aqueous extract utilized for the fabrication of AgNPs. The analytical results revealed that DFPAE-AgNPs were crystalline, spherical in shape in the size range of 10–50 nm, and composed of 73.90% weight of a silver element. The IC50 value of the DFPAE-AgNPs is evaluated as 37.98 ± 0.21 µg mL −1 with a HepG2 cell line. Acridine orange- ethidium bromide (AO-EtBr) staining and nuclear acid staining assays demonstrated the dose-dependent (10–50 µg mL −1 ) apoptotic increase phenomenon of the DFPAE-AgNPs in the HepG2 cell line at 24 h. The current study suggested DFPAE as a vital, reliable, and active phytoconstituents for the fabrication of AgNPs with anticancer potentials in a rapid and eco-friendly way. Further meticulous investigation on the DFPAE-AgNPs behavioral nature is recommended to make use of these as alternatives to synthetic drugs in wider anticancer applications. Graphical Abstract: ga1 Highlights: Utilization of non-edible dragon fruit waste in the synthesis of silver nanoparticles (AgNPs). Dragon fruit peel extracts capable of reducing AgNO3 to AgNPs at 29 ± 2 °C. Synthesized AgNPs were crystalline, spherical shape with 10–50 nm size. AgNPs exhibited potential anticancer activity on HepG2 cell line under in vitro conditions.